2022
DOI: 10.2147/ijgm.s364708
|View full text |Cite
|
Sign up to set email alerts
|

The Overexpression of Fibronectin 1 Promotes Cancer Progression and Associated with M2 Macrophages Polarization in Head and Neck Squamous Cell Carcinoma Patients

Abstract: Purpose This study aimed to investigate the biological roles of fibronectin 1 (FN1) in head and neck squamous cell carcinoma (HNSCC) and its effects on macrophage M2 polarization. Methods We analyzed FN1 expression pattern and examined its clinical relevance in HNSCC progression by bioinformatic analysis. Small interfering RNA (siRNA) was utilized to silence FN1 in HNSCC cells. Cell counting kit-8 (CCK-8) assay, colony formation assay, Transwell assay and wound healing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 62 publications
0
11
0
Order By: Relevance
“…High fibronectin expression has been associated with inferior survival for patients with other HPV-associated cancers such as cervical cancer [ 25 ] and head/neck cancer [ 26 ]. In vitro, models of HPV-associated cancers have linked fibronectin overexpression to increased activation of the focal adhesion kinase signaling pathway, which promotes cancer cell migration [ 27 ] and the polarization of anti-inflammatory M2 macrophages [ 28 ] that may promote tumor progression [ 29 ]. Consistent with these findings for other HPV-associated malignancies, our data here provide further support for fibronectin as an unfavorable prognostic biomarker for anal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…High fibronectin expression has been associated with inferior survival for patients with other HPV-associated cancers such as cervical cancer [ 25 ] and head/neck cancer [ 26 ]. In vitro, models of HPV-associated cancers have linked fibronectin overexpression to increased activation of the focal adhesion kinase signaling pathway, which promotes cancer cell migration [ 27 ] and the polarization of anti-inflammatory M2 macrophages [ 28 ] that may promote tumor progression [ 29 ]. Consistent with these findings for other HPV-associated malignancies, our data here provide further support for fibronectin as an unfavorable prognostic biomarker for anal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In this report, we provide compelling evidence that IL‐17A lies downstream of Fn1. Both Fn1 (Bazan‐Socha et al., 2018 , Hamsten et al., 2016 , Wang et al., 2017 , Zhou et al., 2022 ) and IL‐17A (Akbay et al., 2017 , Cai et al., 2019 , Hagner et al., 2021 , Salazar et al., 2020 ) have been shown to promote inflammation and tumour progression. Interaction of IL‐17A with its receptor, which is expressed on a variety of cell types (including tumour cells and non‐tumour cells), causes secretion of proinflammatory cytokines such as IL‐6, various chemokines and factors that promote tumour progression.…”
Section: Discussionmentioning
confidence: 99%
“…The aberrant expression of FN1 has been proven to be associated closely with the invasion and prognosis of a variety of solid tumors, including renal, gastric, and lung cancers 32,33 . FN1 upregulation was strongly associated with M2 macrophage polarization and might be implicated in the progression of HNSCC through the Akt and MAPK signaling pathways 34 . Besides, Zhang et al demonstrated that FN1 increased the sensitivity of OS cells to cisplatin to promote cell apoptosis 35 .…”
Section: Discussionmentioning
confidence: 99%
“… 32 , 33 FN1 upregulation was strongly associated with M2 macrophage polarization and might be implicated in the progression of HNSCC through the Akt and MAPK signaling pathways. 34 Besides, Zhang et al demonstrated that FN1 increased the sensitivity of OS cells to cisplatin to promote cell apoptosis. 35 These studies suggest that these three MSGs have a major role in tumor progression.…”
Section: Discussionmentioning
confidence: 99%